Kepadatan tulang santriwati berhubungan dengan profil antropometri - Fillah Fithra Dieny; Firdananda Fikri Jauharany; A Fahmy Arif Tsani; Ayu Rahadiyanti (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2020)
Santriwati’s bone mass density was associated with the anthropometric profileBackground: One group of female adolescents who had nutritional problems was Islamic boarding school students, namely santriwati. Low intake was supported by a poor diet profile that had a risk of developing osteopenia. The problem of osteopenia in adolescents could affect long-term calcium deposits and had an impact on old age and a high risk of osteoporosis.Objective: This study aims to examine the relationship between diet profiles and anthropometric profiles with bone density in female students.Methods: A cross-sectional study of 76 female students who were selected using a simple random sampling technique. Anthropometric profiles measured were body mass index, body fat percent, and waist circumference. Bone density was measured using Dual Energy X-Ray Absorptiometry (DXA). Nutrient intake profiles were obtained based on intake interviews used food recall form 6x24 hours. Data were analyzed using Spearman correlations.Results: Most female students had normal nutritional status, and 14 female students (18.4%) had low bone density. The intake of energy, macronutrients (protein, fat, and carbohydrate), and micronutrients (phosphorus, calcium, and vitamin D) of female students were insufficient. There was a relationship between body mass index (p=0.036; r=0.241) and percent body fat (p=0.027; r=0.254) with bone density. However, the nutrient intake factor has no relationship with bone density (p>0.05).Conclusions: Body mass index and body fat percent are positively correlated with female bone density.